Role of Shatadhauta Ghrita and Medicated Ghee Based Non-Adherent Dressing with Yashad Bhasma in the Management of Dur-Dagdha Vrana/Scalds Burn (Second Degree Burn) - Chaturbhuj; Gopikrishna BJ; Sahanasheela KR (International Journal of Ayurveda and Pharma Research, 2023)
A case of 3-years old child presented with complaints of blister over the anteromedial aspect of the left ankle and over the dorsum aspect of left foot due to scalds burn by fall of hot curry 1 day ago. In Ayurveda, Dagdha Vrana explained in Sushruta Samhita with details regarding classification, clinical features and detailed management according to types, therapeutic burns also have been described in Sutra Sthana “Agnikarma Vidhi Adhyaya”. Aim and objectives: To see the role of Shatadhauta Ghrita and medicated Ghee based non-adherent dressing with Yashad Bhasma in the management of Dur-Dagdha Vrana (scalds burn). Material and methods: Shatadhauta Ghrita external application followed by medicated Ghee based non-adherent dressing with Yashad Bhasma over the Dur-Dagdha Vrana site for 10 days once a day. Results: There was complete cure of the Dur-Dagdha Vrana within 10 days of treatment. Conclusion: In current case, Shatadhauta Ghrita application due to its Pitta-Vatahara, Vrana Shodhana, Vrana Ropana, Daha Prashamana and Vedanasthapana properties helps to reduce the burning sensation and pain over the Dur-Dagdha Vrana site. Medicated ghee based non-adherent dressing with Yashad Bhasma helps in Vrana Shodhana and Vrana Ropana (healing).